Improving the Effectiveness of Heat Pipe solar Connector by using Nano fluid - Mohammed Ridha H Alhakeem (ITScience (Information Technology and Science), 2022)
This article provides a thorough analysis of current developments in the use of nano fluids in the sun collectors with heat pipes. Theoretical, numerical, and experimental papers that are current and relevant to the Applications of nanotechnology in this class of solar collectors. To provide a thorough overview of the effect of the nano fluid in enhancing heat pipe solar collectors, a large body of literature has been thoroughly researched and summarized. The effectiveness of heat pipe solar collectors can be significantly increased by using nano fluid, it was discovered certain tools.